(untitled) (IJABER. International Journal of Arts-Based Educational Research, 2024)
This article examines soundwalking at the Progreso-Nuevo Progreso International Bridge as an arts-based educational research (ABER) method, specifically through the lens of Sounding Art Practice as Research (SAPAR). By immersing participants in border soundscapes, the study investigates the socio-cultural and political dynamics of the U.S.-Mexico border and their pedagogical implications. Through deep listening, participants explore how sound constructs, disrupts, and reflects borders, offering new sensory-based approaches to art education. The practice emphasizes the role of sound in fostering critical thinking, sensory awareness, and deeper cultural understanding in students. Additionally, it highlights how soundwalking can be used as an ethical and sensitive tool to document the realities of border life without visual exploitation, creating immersive, reflective experiences. The study also incorporates spectrogram analysis, visualizing the harmonic movements between the U.S. and Mexico, further illustrating the complex intersections of sound, identity, and place in borderlands.